Kinematics, recrystallization mechanisms and Ar-Ar ages in Cal shear zone, Curitiba microplate, central Mantiqueira province, Brazil - Barros, Carlos Eduardo de Mesquita; Fassbinder, Elvo; Vasconcelos, Paulo Marcos; Fiori, Alberto Pio; Bueno, Nicole Favoreto de Souza (Boletim Paranaense de Geociências, 2024)
Mylonites and ultramylonites derived from plastic deformation of gray quartzo-feldspathic rocks and granites are described in the Cal shear zone, western margin of the Curitiba microplate, central Mantiqueira province. Ultramylonites and mylonites occur along several hundred meters along the São Jorge quarry main front. Mylonite foliation strikes N40E/90, while stretching lineation strike N40/15. Sigmoidal structures, S/C/C' surfaces, mica fish and secondary foliation in quartz ribbons indicate sinistral sense. Quartzo-feldspathic mylonites and leucogranitic mylonites are interlayered in subparallel steep dipping portions forming a conspicuous banding. Quartz recrystallization controlled by grain boundary migration and subgrain rotation suggest temperatures higher than 500 ºC in the plastic shear zone. These temperature conditions are coherent with the feldspars recrystallization. The presence of veins of quartz suggests that pressure solution was a subordinated deformation mechanism. Ar-Ar dating of feldspar from ultramylonites yielded an age of 608 Ma for the Cal strike-slip shear zone. A thermotectonic phase attributed to brittle-plastic reactivation during dextral transcurrent shear is thought to have occurred at ca. 553 Ma.